Pharmacological treatment of depression in patients with brain tumors - Knabbe, Johannes; Kowalski, Thomas; Seliger, Corinna (International journal of cancer, 2024)
Patients with brain tumors suffer from intense psychosocial distress. Although the prevalence of depressive symptoms in patients with brain tumors is high, the pharmacological antidepressant treatment of those patients is not well defined and results from clinical trials are largely missing. In this review, we describe the current standard of evidence and clinical guidelines for the pharmacological treatment of depression in brain tumor patients. We present specific side effects and interactions that should guide treatment decisions. Furthermore, we provide evidence for the diagnosis, screening and risk factors for depression in brain tumor patients and we elaborate on potential antineoplastic effects of antidepressant drugs and ongoing clinical trials. Antidepressant drugs should not be withheld from patients with brain tumors. Future clinical trials should explore the effectiveness and side effects of antidepressants in this specific patient population.
Veröffentlicht: 28 June 2024
Gesehen am 29.01.2025